2020
DOI: 10.1161/jaha.120.017196
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Diversity in Cardiology: A Survey of Cardiology Fellowship Training Program Directors

Abstract: Background The lack of diversity in the cardiovascular physician workforce is thought to be an important driver of racial and sex disparities in cardiac care. Cardiology fellowship program directors play a critical role in shaping the cardiology workforce. Methods and Results To assess program directors’ perceptions about diversity and barriers to enhancing diversity, the authors conducted a survey of 513 fellowship program directors or associate direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…These findings suggest that program directors believe that they have the means to employ methods that meaningfully increase diversity within their programs. As in previous studies, most fellowship directors claimed to support diversity, although a previous study found that less than half of directors reported having a formalized plan to achieve this goal [11][12]. Achieving meaningful increases in diversity in the field of cardiology may require fellowship program directors to identify and implement such strategies.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…These findings suggest that program directors believe that they have the means to employ methods that meaningfully increase diversity within their programs. As in previous studies, most fellowship directors claimed to support diversity, although a previous study found that less than half of directors reported having a formalized plan to achieve this goal [11][12]. Achieving meaningful increases in diversity in the field of cardiology may require fellowship program directors to identify and implement such strategies.…”
Section: Discussionmentioning
confidence: 89%
“…However, PDs remain unsure how to implement the desire for diversity in the process of selecting candidates and creating a rank list [ 12 ]. In fact, a previous survey of fellowship directors showed that only 6% of respondents considered diversity to be a top-three priority when forming the rank list [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations